Characterization of composites based on biodegradable poly(vinyl alcohol) and nanostructured fly ash with an emphasis on polymer–filler interaction. (October 2016) - Patil, Akshata G; Selvakumar, M; Anandhan, S
A thermal power station fly ash (FA) was mechanochemically activated by high-energy ball milling that yielded nanostructured FA. This nanostructured FA was incorporated into biodegradable poly(vinyl alcohol) (PVA) matrix by solution mixing and ultrasonication. Transmission electron micrographs revealed that the smooth spherical particles of FA were changed into irregular and rough ones; in addition, the particle size of FA was reduced to a few hundred nanometers, and its specific surface area value increased after the high-energy milling process. All these factors, in turn, led to a thermodynamically favorable interaction between the mechanochemically activated FA and PVA as evidenced by Fourier transform infrared spectroscopy. The incorporation of a very small amount of the nanostructured FA led to an increase in crystallinity of the polymer matrix. The glass transition temperature of the PVA matrix increased by about 18°C when 5 wt% of the nanostructured FA was used as the reinforcement.